2023
DOI: 10.3390/ijms24032712
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroles as a Potential Biomarker for Oxidative Stress Disorders

Abstract: Redox imbalance or oxidative stress that results from both environmental and genetic factors is observed in patients with schizophrenia. Therefore, identifying markers of oxidative stress in the early stages of psychosis and using antioxidant treatments as an adjuvant to antipsychotics has important implications. The reaction of p-N,N-dimethylaminobenzaldehyde (DMAB) with pyrrole moieties has been well studied for well over a century for use as a marker of oxidative stress dysregulation. Throughout this time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…High levels of this molecule have been detected in the urine of patients with schizophrenia and particularly in those who do not possess the homozygous MTHFR 677 polymorphism [81,126]. Elevated urine HPL levels are reportedly reduced by vitamin B6 (PLP) and zinc supplementation, though the exact mechanism of this effect is yet to be established [127]. Given the relevance of many of the above-discussed downstream effects of the serine-glycine pathway for schizophrenia, serine and glycine and HPL have potential roles as biomarkers for schizophrenia, and preliminary research on their role in this disorder has indeed been reported in the literature [128].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of this molecule have been detected in the urine of patients with schizophrenia and particularly in those who do not possess the homozygous MTHFR 677 polymorphism [81,126]. Elevated urine HPL levels are reportedly reduced by vitamin B6 (PLP) and zinc supplementation, though the exact mechanism of this effect is yet to be established [127]. Given the relevance of many of the above-discussed downstream effects of the serine-glycine pathway for schizophrenia, serine and glycine and HPL have potential roles as biomarkers for schizophrenia, and preliminary research on their role in this disorder has indeed been reported in the literature [128].…”
Section: Discussionmentioning
confidence: 99%
“…Pyrrole was the only VOC that we found to be significantly decreased in the fecal headspace of SBS animals. The substance was first comprehensively studied in 1938 [43]. Pyrroles are characterized by a ring structure composed of four carbon atoms and one nitrogen atom.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of this molecule leads to metabolic crisis in mitochondria [60]. High levels of HPL have been detected in the urine of patients with schizophrenia who do not possess the homozygous MTHFR 677 polymorphism [61], and significant correlates for heightened HPL have also been linked to multiple symptoms of schizophrenia [15,45,62,63].…”
Section: Functional Interactions Of Biomarker Findings For the Mthfr ...mentioning
confidence: 99%